Low intensity pulsed ultrasound in orthodontic tooth movement: Low intensity pulsed ultrasound dalam pergerakan gigi ortodonti - Karima Qurnia Mansjur; Mansjur Nasir; Zilal Islamy Paramma; Isma Wahyuni (Makassar Dental Journal, 2021)
Orthodontic treatment that takes a long time carries a large risk of complications such as caries or root resorption. Various surgical and nonsurgical interventions have been performed, but non-surgical interventions are currently not widely accepted by orthodontists. Low Intensity Pulsed Ultrasound (LIPUS) is a form of non-invasive technology that has been used in the medical field for more than six decades. In the field of dentistry, LIPUS stimulation has been studied, among others, to improve bone remodelling, regeneration of cementum, gingiva and periodontal ligament. This article aims to review the mechanism of LIPUS in orthodontic tooth movement. This review is expected to become a clinical practice guide to shorten the duration of orthodontic treatment using LIPUS in the future.